An investigation of the principal's leadership role in a successful rural school in Namibia - Tjivikua, Uerivangera Chris (Rhodes University, Faculty of Education, Department of Education, 2007)
Rural schools are faced with numerous challenges and are often perceived to be academically unsuccessful. However, in spite of this perception there are some which manage to beat the odds by being academically successful year after year. This peculiar phenomenon of 'unequal performance' among rural schools struck my interest; hence my decision to investigate what it is that successful rural schools do to keep afloat in a turbulent environment where others around them collapsed. As the literature suggests that leadership play a key role in the success of an organisation, I focused my study on how the leadership role of the principal makes a rural school thrive. The study is situated in the interpretive paradigm and attempts to reveal participants' perceptions and experiences of the principal's leadership. My participants were the principal, circuit inspector, the School Board Chairperson, a Head of Department and the LRC president. These people were purposefully selected; the principal was selected because he is the one executing the roles hence he would be better informed about them while the others due to the positions they occupy, work closely with the principal. The research is a case study as it focused on a single case, and for data generation I employed semi-structured interviews, observation and document analysis. The study revealed various characteristics that describe the leadership role of the principal. An overarching characteristic that emerged is that the principal is a balanced leader - he focuses on both task completion and consideration for people. Different characteristics that emerged from this balance leadership portrayed the principal of Ruacana Senior Secondary School to be a transformational and an instructional leader who believes that teaching and learning are the central activities of a school. Moreover he has been painted to be a team player and a servant leader who holds and practices the principle of ubuntu. The principal has also been described as a strategic and exemplary leader. It emerged that his exemplary leadership has moulded the practices of teachers and learners into a shared culture that supports academic excellence. The findings also depicted a paradoxical picture of the principal in that while he exhibits democratic procedures he is also perceived to be autocratic.
Keywords: Rural schools -- Namibia; School principals -- Namibia; School management and organization -- Namibia; Educational leadership -- Namibia